Quality improvement of community pharmacy services: a prioritisation exercise. (27th March 2017) - Newlands, Rumana S; Power, Ailsa; Young, Linda; Watson, Margaret
Abstract: Objectives: Effective strategies are needed to translate knowledge (evidence) into practice to improve the quality of community pharmacy services. We report the first step of a novel knowledge translation process which involved the systematic identification and prioritisation of community pharmacy services in Scotland which were perceived to require improvement and/or guideline development. Methods: This process involved three stages and a stakeholder group comprising community pharmacists, policy makers, lay and pharmacy organisation representatives. A modified nominal group technique (NGT) was used for topic generation (August 2013) followed by an electronic Delphi survey (eDelphi), October–December 2013) and topic rationalisation (December 2013) based on feasibility, acceptability, and potential impact for practice improvement. Key findings: In total, 63 items were identified during the modified NGT which were categorised into 20 topics to form the starting point of the eDelphi. In total, 74 individuals (mostly community pharmacists) indicated an interest in the eDelphi, which achieved response rates of 63.5%, 67.6%, and 70.3%, respectively in Rounds 1, 2, and 3. Consensus was achieved with six topics: promoting the appropriate sale and supply of over-the-counter medicines; patient counselling for prescribed medication; pharmaceutical care to promote medication adherence; promotion and delivery of a Minor Ailment Scheme; pharmaceutical care of vulnerable patients; and effective use of community pharmacy workforce. Of these, the priority topic selected for the next stage of the programme was promoting the appropriate sale and supply of over-the-counter medicines . Conclusions: This study adopted a systematic, inclusive, and rapid approach to identify priorities for community pharmacy practice improvement in Scotland.